How to make money using etsy : a guide to the online marketplace for crafts and handmade products - Adam, Tim, 1979- (Hoboken, N.J. : Wiley, 2011)
'In a world where most products are manufactured by machines, Etsy offers an online platform for makers of handmade products and crafts to market and sell their goods to a vast network of buyers who demand unique, genuine products. To date, the site has attracted over 400,000 sellers who collectively have sold 1.3 million items, generating $180.6 million in revenue. The only resource of its kind, How to Make Money Using Etsy--written by Tim Adam who has successfully been selling his products all over the world through his Etsy shop since 2007--guides readers step-by-step through the many stages of selling online. How-to topics include: Establish your Etsy shop Effectively photograph your products Post your products to optimize visibility and increase sales Brand your business Use social media like blogs, Twitter, and Facebook to connect with buyers and grow your business'--
Includes index.
Keywords: Etsy (Firm).; Handicraft industries -- Management; Handicraft -- Marketing; Selling -- Handicraft; BUSINESS & ECONOMICS / Entrepreneurship